THE PARTIALIZATION AS A METHOD FOR DECONTAMINATION OF MOTOR TESTS AND DISCRIMINATION OF VARIOUS FORMS MANIFESTATION OF MUSCULAR FORCE - Durica Amanovic; Zarko Kostovski; Milija Ljubisavljevic (Sport Scientific And Practical Aspects, 2025)
The aim of this study is to define partialization as a method for determining and monitoring of measuring muscle force and the development of different forms of force under the influence of the curriculum of Special Physical Education (SPE). In the paper the partialization (corrections) of all variables was made of the measured (raw) data. In this way, the differences among the respondents in the morphological area are neutralized and the results obtained in the performed tests are brought to a level of force. Based on the corrected values it can be concluded that the applied partialisations of the measured dimensions for decontamination of morphological impact on the manifestation of various forms of muscular force indicated the obtaining of a clean structure of motor space and that the applied curriculum of SPE significantly influenced the changes in size of various forms of force. Determination of development tendencies and resizing of forces at the individual level helps optimize and adequately manage sports training.